PELATIHAN DAN PENDAMPINGAN PEMANFAATAN APLIKASI E-COMMERCE BERBASIS WORDPRESS BAGI WARGA CIPOCOK KOTA SERANG - Jaka Wijaya Kusuma; Hamidah Hamidah; Surti Zahra; Nugrahini Kusumawati; Siti Fatonah; Nursoleh Nursoleh (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
This PKM is in the form of training and mentoring. The series of activities begins with giving invitation letters to the surrounding residents. Training activities consist of 2 places, namely in the first place is a special training of mothers or women and the second place is assistance for fathers or youths. The number of participants who participated in this construction was as many as 18. The type of software used is WordPress which is accessed online through http://id.wordpress.com. All participants are very enthusiastic about participating in activities. From the questionnaire achieved, there were as many as 70% of participants successfully participated in activities without any obstacles, as many as 20% could follow the activity with a little help and guidance; lastly, as many as 10% of participants had difficulty participating in training caused by not having or carrying laptop facilities